Peran Saudara Kandung terhadap Permasalahan Gizi Balita di Lingkungan Keluarga - Yunita Wulandari; Evi Martha (Malahayati Nursing Journal, 2025)
ABSTRACT Nutritional problems in toddlers are influenced by various factors. The presence of siblings is one of the factors that play a role in the nutritional problems of toddlers. Close birth distance causes the care of children in one family to be not optimal. Find out the causes of under-five nutritional problems among siblings in the same family.The study used a systematic review method using PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis). Material collection was carried out using two search engines, Google Scholar and Science Direct, which were accessed via https://remote-lib.ui.ac.id/. 1250 articles from Google Scholar and 63 articles from Science Direct were obtained. Eight articles were reviewed. Keywords used "Siblings" "Contribution" "Under-Five Children" "Nutrition" "Problems". The sibling factor contributes to under-five children's nutrition problems. The number of siblings affects the feeding patterns of children under five in a family. The close birth distance also contributes to the emergence of nutritional issues due to inadequate food intake given to children in one family, especially those from low economic backgrounds. Siblings contribute to nutritional problems in children under five, especially if the birth distance is close enough. There is a need to educate young families on birth spacing and educate parents on how to manage adequate nutrition for children under five who are more than one person in a family. Keywords: Siblings, Nutrition Problems, Stunting, Nutritional Adequacy  ABSTRAK Keberadaan saudara kandung menjadi salah saatu faktor yang berperan pada permasalahan gizi balita. Jarak kelahiran yang dekat menyebabkan pengasuhan terhadap anak-anak dalam satu keluarga menjadi tidak optimal. Mengetahui gambaran penyebab permasalahan gizi balita di antara saudara kandung dalam satu keluarga. Penelitian menggunakan metode systematic review dengan menggunakan PRISMA (Prefered Reporting Items for Systematic Review and Meta-Analysis). Pengumpulan materi dilakukan menggunakan dua mesin pencari yaitu Google Scholar dan Science Direct. Didapatkan 1313 artikel sumber dan delapan artikel yang direview. Kata kunci yang digunakan “Siblings” “Contribution” “Under-Five Children” “Nutrition” “Problems”. Faktor saudara kandung berperan terhadap permasalahan gizi balita. Banyaknya jumlah saudara kandung mempengaruhi pola pemberian makan pada anak balita dalam satu keluarga. Dekatnya jarak kelahiran juga berperan pada munculnya masalah gizi akibat ketidakcukupan asupan makanan yang diberikan pada anak-anak dalam satu keluarga terutama yang berasal dari ekonomi rendah. Saudara kandung mempunyai kontribusi pada terjadinya masalah gizi balita, terutama jika jarak kelahiran cukup dekat. Perlu adanya edukasi bagi keluarga untuk dapat mengatur jarak kelahiran serta edukasi bagi para orang tua tentang bagaimana mengatur asupan gizi yang cukup untuk anak balita yang berjumlah lebih dari satu orang dalam satu keluarga. Kata Kunci: Balita, Saudara Kandung, Masalah Gizi, Stunting, Kecukupan Gizi